Pengaruh Orientasi Pasar,Orientasi Kewirausahaan,dan Kreativitas Strategi Pemasaran yang Diintervening Inovasi Terhadap Kinerja Bisnis di Dama Group - Meagika Surya Putri; Nofrivul Nofrivul; Mirawati Mirawati; Khairul Marlin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The aim of this research is to determine the influence of market orientation, entrepreneurial orientation and marketing strategy creativity intervening with innovation on business performance in the Dama Group. The research was conducted using a quantitative approach. The data analysis technique uses Structural Equation Modeling (SEM) analysis with smartPLS version 4.1.0.0. Based on the research results, it was found that market orientation variables, entrepreneurial orientation and marketing strategy creativity had an influence on business performance variables in the Dama Group. The variables market orientation, entrepreneurial orientation and marketing strategy creativity influence the innovation variable at Dama Group. The innovation variable has no effect on the business performance variable at Dama Group. The market orientation variable has no effect on business performance where innovation intervenes at Dama Group. The entrepreneurial orientation variable has no effect on business performance where innovation intervenes at the Dama Group. The marketing strategy creativity variable has no effect on business performance where innovation intervenes at Dama Group.